Effect of Ceramic Surface Treatment and Adhesive Systems on Bond Strength of Metallic Brackets - Patrapan Juntavee; Hattanas Kumchai; Niwut Juntavee; Dan Nathanson (International Journal of Dentistry)
Objective. This study evaluated the effect of ceramic surface treatments on bond strength of metal brackets to machinable ceramics and veneering porcelain using different adhesive resins. Materials and methods. Machined ceramic specimens (10 × 10 × 2 mm) were prepared from Vitablocs mark II (Vita) and IPS e.max® CAD (Ivoclar). Layered porcelain fused to metal (IPS d.Sign®, Ivoclar) was used to fabricate PFM specimens (n = 60/group). Half of specimens were etched (9.6% HF, 15 sec), and the rest were nonetched. Three resin bonding systems were used for attaching metal brackets (Victory series™ APC II, 3M) to each group (n = 10): Transbond™ XT (3M), Light Bond™ (Reliance), or Blugloo™ (Ormco), all cured with LED curing unit (Bluephase G1600, Vivadent) for 50 s each. Specimens were immersed in deionized water at 37°C for 24 hours prior to shear bond testing (Instron) at crosshead speed of 0.5 mm/min. Debond surface of ceramic and bracket base was examined for failure mode (FM), Ceramic Damage Index (CDI), and Adhesive Remnant Index (ARI). ANOVA and post hoc multiple comparisons were used to analyze the differences in bond strength. The chi-squared test was used to determine significance effect of FM, CDI, and ARI. Results. Significant differences in shear bond strength among group were found (p≤0.05) related to ceramic, surface treatment, and resin cement. Conclusion. Bond strength of bracket to ceramic is affected by type of ceramic, resin cement, and ceramic surface conditioning. Etching ceramic surface enhanced ceramic-bracket bond strength. However, bond strengths in nontreated ceramic surface groups were still higher than bond strength required for bonding in orthodontic treatment.